MAKNA â€œMEMANCINGâ€ BAHASA BALI DIALEK DESA LEMBONGAN: KAJIAN METABAHASA SEMANTIK ALAMI - I Wayan Ana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
[Title: Meaning of â€œMemancingâ€Balinese Language of Lembongan Village Dialect : The Study of Natural Semantics Metalanguage] The word â€˜memancingâ€ (fishing) can be found in most languages in the world and this word is unique in the Balinese Language of Lembongan Village Dialect as it various hyponymies. This research is intended to recognize and explain the meaning of â€œmemancingâ€ in Balinese of Lembongan Village Dialect and to preserve the lexicons that are almost extinct due to the rapid development of tourism. To analyze the problems of this research, the NSM theory is applied to the concept of semantic primitive, polysemy, allolection, and universal syntax. The phases of NSM theory in analyzing the meaning of â€œmemancingâ€ in BBDL are configurations of components to find out distinctive features, and explication to study the information on the meaning of â€œmemancingâ€ which includes entity imposed by the treatment, the equipment use, the uniqueness of movement and the expected proceeds. From the analysis, it is found that there are seven lexicons having the meaning of â€œmemancingâ€ with distinctive features, namely: memelas, ngerumik, ngulur, melok, muduk, maidang dan nyogonang.